Sensitivity of A. islandica and M. edulis towards environmental changes: a threat to the bivalves - Hiebenthal, Claas (2009)
As a major green house gas, CO2 causes global warming which further induces changes in other climate parameters like precipitation and salinity. Additionally as about one-third of the atmospheric CO2 is absorbed by surface waters, the oceans become acidified. Bivalve shell production is costly and should therefore be sensitive to environmental stress. Water pCO2, salinity and temperature changes may be factors that increase physiological stress and thus, can reduce fitness, muscle strength, shell growth, shell stability and finally the bivalves’ ecological performance. The improvement of climate models requires a better understanding of climate history. The ratios of stable Ca isotopes and of divalent substituents of Ca (e.g. Mg and Sr) in bivalve shells depend on seawater temperatures and can therefore theoretically be used as archives of past seawater climates. In two 2-factorial experimental approaches (temperature vs. salinity, temperature vs. pCO2), this work investigates the influence of water temperature, salinity and pCO2 on shell growth, mortality, condition index (Ci = soft tissue weight / shell weight), lipofuscin content in the soft tissue (by fluorometry), shell stability (with a texture analyzer), shell Mg / Ca and Sr / Ca ratios (by optical emission spectrometry) and shell Ca isotope fractionation (Δ44/40Ca, by mass spectrometry) of the two bivalve species Arctica islandica and Mytilus edulis. Additionally, in a feeding assay, we tested the defence capability of M. edulis towards predation by starfish Asterias rubens. Lipofuscin accumulation, growth rates and mortalities indicate that M. edulis is rather an estuarine than a fully marine species. Independent of the respective salinity, however, condition and growth of this species are strongly controlled by temperature. In the Baltic Sea, a positive temperature effect on shell stability will presumably be stronger than a negative salinity effect. A. islandica is a species adapted to high salinity and low temperatures. This could be shown by ...